Bonding film and light-transmitting laminate
By controlling the embossing characteristics of the surface of the bonding film, the problems of degassing stability and edge sealing in the light-transmitting laminate are solved, and efficient gas discharge and edge sealing are achieved, thereby preventing heavy shadows in the head-up display.
Patent Information
- Application Number
- CN202211699131.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-22
- Filing Date
- 2020-08-07
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-08-07
AI Technical Summary
The conventional bonding film is prone to problems with degassing stability and edge sealing when forming the light-transmitting laminate, and may lead to heavy shadows in the head-up display.
By controlling the embossing characteristics of the surface of the bonding film, the A2/A1 value is 1 or less, the Sz value is between 30 um and 90 um, and an embossing with regular or irregular patterns is formed on the surface to improve the degassing stability and edge sealing of the film.
The degassing stability and edge sealing in the light-transmitting laminate are achieved, and bubble generation is reduced, and heavy shadows in the head-up display are prevented.
Smart Images

Figure CN116198189B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 2020800564563, application date August 7, 2020, and invention name “Joining film and light-transmitting laminate comprising the same”. Technical Field
[0002] [CROSS-REFERENCE TO RELATED APPLICATIONS]
[0003] This application claims the benefit of Korean Patent Application No. 10-2019-0097413 filed on Aug. 9, 2019, Korean Patent Application No. 10-2019-0103615 filed on Aug. 23, 2019, Korean Patent Application No. 10-2020-0008459 filed on Jan. 22, 2020, Korean Patent Application No. 10-2019-0105222 filed on Aug. 27, 2019, and Korean Patent Application No. 10-2019-0145153 filed on Nov. 13, 2019, the entire contents of which are incorporated herein by reference.
[0004] The implementation example relates to a bonding film and a light-transmitting laminate including the same. Background Art
[0005] Polyvinyl acetal is used as an intermediate layer (film for bonding glass) of bonding glass (safety glass) or light-transmitting laminate. Bonding glass is mainly used for windows of buildings, exterior materials, automobile window glass, etc. Even if the bonding glass is damaged, its fragments will not scatter, and even if the bonding glass is hit with a certain intensity, it is not allowed to penetrate. With the above characteristics, the bonding glass can ensure stability to minimize damage or injury to objects or people inside it.
[0006] When the bonding film is used as a head-up display (HUD) film, a wedge-shaped film having a predetermined wedge angle in cross section may be used to prevent ghosting.
[0007] A plurality of fine embossing patterns are formed on the surface of the bonding film to prevent adhesion between interlayers and to improve workability (slidability with the glass plate) when overlapping the glass plate and the interlayer and degassing stability during bonding with the glass plate.
[0008] When a bonding film with embossed patterns is used for bonding, interference fringes or bubbles may occur on the bonded glass due to the influence of the embossed patterns on both sides of the film, which may reduce visibility. In addition, when glare occurs, there is a problem that workability deteriorates.
[0009] (Prior art literature)
[0010] Korean Patent No. 10-1376061
[0011] Japanese Patent Publication No. 2001-220183 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] An object of the implementation example is to provide a bonding film that has improved degassing stability, edge sealing characteristics, etc. and can suppress ghosting in a head-up display, and a light-transmitting laminate including the bonding film.
[0014] Means used to solve problems
[0015] In order to achieve the above object, a bonding film according to an embodiment of the present specification includes a surface having embossed patterns, and the A2 / A1 value of the surface having embossed patterns is 1 or less.
[0016] The Sz value of the surface on which the embossing is formed may be greater than or equal to 30 um and less than or equal to 90 um.
[0017] The Sz value of the surface on which the embossing is formed may be 40 um or more and 80 um or less.
[0018] The A1 value may be greater than 0.5.
[0019] The A2 value may be less than 0.6.
[0020] The bonding film may be a single-layer film or a laminated film of two or more layers.
[0021] The bonding film may contain a polyvinyl acetal resin.
[0022] At least a part or the entirety of the cross section of the bonding film may be wedge-shaped.
[0023] A light-transmitting stack according to another embodiment of the present invention includes: a first light-transmitting layer; a bonding film located on a surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film, wherein the bonding film includes a surface with an embossed surface, and the A2 / A1 value of the surface with the embossed surface is less than 1.
[0024] Regarding the light-transmitting laminated body, the total number of bubbles generated in three light-transmitting laminated bodies having a width of 300 mm and a length of 300 mm may be 5 or less.
[0025] Any one selected from the group consisting of the first light-transmitting layer, the second light-transmitting layer, and a combination thereof may be aged glass.
[0026] A mobile device according to yet another embodiment of the present invention includes the light-transmitting laminate.
[0027] In order to achieve the above object, a bonding film according to another embodiment disclosed in the present specification includes a surface on which embossing having a regular or irregular pattern is formed.
[0028] The surface formed with the embossing has Mr1 value and Mr2 value.
[0029] The rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0030] The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value.
[0031] The peak-to-valley distribution value (Spv) is represented by the following Formula 1. The peak-to-valley distribution value of the surface on which the embossing is formed may be 0% or more and 25% or less.
[0032] Formula 1:
[0033] Spv=Mr1-rev_Mr2
[0034] In the first formula, the Spv is a peak-to-valley distribution value, and the rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0035] The Mr1 value may be greater than 10%.
[0036] The Sz value of the surface of the bonding film on which the embossing is formed may be 30 um or more and 90 um or less.
[0037] The bonding film may be a single-layer film or a laminated film of two or more layers.
[0038] The bonding film may contain a polyvinyl acetal resin.
[0039] At least a part or the entirety of the cross section of the bonding film may be wedge-shaped.
[0040] A light-transmitting laminate according to another embodiment of the present invention includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film.
[0041] The bonding film includes a surface on which embossing having a regular or irregular pattern is formed.
[0042] The surface formed with the embossing has Mr1 value and Mr2 value.
[0043] The rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0044] The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value.
[0045] Regarding the light-transmitting laminated body, the total number of bubbles generated in three light-transmitting laminated bodies having a width of 300 mm and a length of 300 mm may be 5 or less.
[0046] Any one selected from the group consisting of the first light-transmitting layer, the second light-transmitting layer, and a combination thereof may be aging glass.
[0047] A mobile device according to yet another embodiment of the present invention includes the light-transmitting laminate.
[0048] To achieve the above object, a bonding film according to another embodiment disclosed in the present specification includes a surface having embossed patterns having a regular or irregular pattern, wherein the DSvk value of the embossed surface represented by the following formula 2 is 6 um or less.
[0049] Formula 2:
[0050] DSvk=S*vk–Svk
[0051] In the second formula, the Svk value is a value evaluated according to ISO_25178.
[0052] The S*vk value is a height value at a point where the areal material ratio Mr2 is in the areal material ratio curve according to ISO_25178.
[0053] The joining film contains 24 to 40% by weight of plasticizer, based on the entire joining film.
[0054] The ratio of the Svk value to the DSvk value of the surface on which the embossing is formed may be 0.1 or more and 1.5 or less.
[0055] The A2 value of the surface on which the embossing is formed may be 0.16 or more and 0.5 or less.
[0056] The Svk value of the surface formed with embossing may be 4 to 10 um.
[0057] The S*vk value of the surface formed with embossing may be less than 12 um.
[0058] The DSvk / Sz value of the surface formed with the embossing may be 0.01 to 0.08.
[0059] The Sz value of the surface formed with the embossing may be 30 to 90 um.
[0060] The bonding film may be a single-layer film or a laminated film of two or more layers.
[0061] The bonding film may contain a polyvinyl acetal resin.
[0062] The bonding film may include a sound insulating layer.
[0063] To achieve the above object, a light-transmitting laminate according to another embodiment disclosed in the present specification includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film.
[0064] The bonding film includes a surface on which embossing having a regular or irregular pattern is formed.
[0065] The DSvk value of the surface on which the embossing is formed, which is represented by the following second formula, is 6 μm or less.
[0066] Formula 2:
[0067] DSvk=S*vk–Svk
[0068] In the above-mentioned second formula, the Svk value is a value evaluated according to ISO_25178.
[0069] The S*vk value is a height value at a point where the support length ratio is Mr2 in the support length ratio curve according to ISO_25178.
[0070] The light-transmitting laminate contains 24 to 40% by weight of the plasticizer based on the entire bonding film.
[0071] After three light-transmitting laminates each having a width of 300 mm and a length of 300 mm are left at 85° C. and 95% RH for 120 hours, the total number of bubbles generated in the three light-transmitting laminates may be 5 or less.
[0072] In order to achieve the above object, a mobile device according to yet another embodiment disclosed in this specification includes the light-transmitting laminated body as a windshield.
[0073] In order to achieve the above object, a bonding film according to an embodiment of the present specification includes a surface having embossed patterns, and an A2 / A1 value of the surface having embossed patterns is 1 or less.
[0074] The bonding film includes a region of increased thickness.
[0075] The increased thickness region has two ends, ie, one end and the other end, and thicknesses of the two ends are different from each other.
[0076] In the bonding film, a wedge angle (θ) is represented by the following Formula 3, and the wedge angle in the increased thickness region may be 0.01 to 0.04°.
[0077] Form 3:
[0078]
[0079] In the third formula, Hb is the thickness of the thicker one of the two ends of the thickness-increased region, Ha is the thickness of the thinner one of the two ends of the thickness-increased region, and w is the width between the two ends of the thickness-increased region.
[0080] The ratio of Ha to w may be greater than or equal to 0.0002 and less than or equal to 0.0015.
[0081] Regarding the bonding film, the increased thickness region may be located in a part or the entirety of the bonding film.
[0082] The Sz value of the surface on which the embossing is formed may be greater than or equal to 30 um and less than or equal to 90 um.
[0083] The Sz value of the surface on which the embossing is formed may be 40 um or more and 80 um or less.
[0084] The A1 value may be greater than 0.5.
[0085] The A2 value may be less than 0.6.
[0086] The bonding film may be a single-layer film or a laminated film of two or more layers.
[0087] The bonding film may contain a polyvinyl acetal resin.
[0088] The bonding film may include a sound insulating layer.
[0089] A light-transmitting laminate according to another embodiment of the present specification includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film.
[0090] The bonding film includes a surface on which embossing is formed.
[0091] The A2 / A1 value of the surface on which the embossing is formed is 1 or less.
[0092] The bonding film includes a region of increased thickness.
[0093] The increased thickness region has two ends, ie, one end and the other end, and thicknesses of the two ends are different from each other.
[0094] Regarding the light-transmitting laminated body, the total number of bubbles generated in three light-transmitting laminated bodies having a width of 900 mm and a length of 300 mm may be 5 or less.
[0095] Any one selected from the group consisting of the first light-transmitting layer, the second light-transmitting layer, and a combination thereof may be aged glass.
[0096] A mobile device according to yet another embodiment of the present specification includes the light-transmitting laminate.
[0097] In order to achieve the above object, a bonding film according to an embodiment of the present specification includes a surface on which embossing having a regular or irregular pattern is formed.
[0098] The surface formed with the embossing has Mr1 value and Mr2 value.
[0099] The rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0100] The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value.
[0101] The bonding film includes a region of increased thickness.
[0102] The increased thickness region has two ends, ie, one end and the other end, and thicknesses of the two ends are different from each other.
[0103] The wedge angle (θ) is expressed by the following third formula.
[0104] Form 3:
[0105]
[0106] In the third formula, Hb is the thickness of the thicker one of the two ends of the thickness-increased region, Ha is the thickness of the thinner one of the two ends of the thickness-increased region, and w is the width between the two ends of the thickness-increased region.
[0107] The wedge angle in the region of increased thickness may be 0.01 to 0.04°.
[0108] The ratio of Ha to w may be greater than or equal to 0.0002 and less than or equal to 0.0015.
[0109] The increased thickness region may be located in a part or the entirety of the bonding film.
[0110] The peak-to-valley distribution value (Spv) is represented by the following Formula 1, and the Spv value of the surface on which the embossing is formed may be 0% or more and 25% or less.
[0111] Formula 1:
[0112] Spv=Mr1-rev_Mr2
[0113] In the first formula, the Spv is a peak-to-valley distribution value, and the rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0114] The Mr1 value may be greater than 10%.
[0115] The Sz value of the surface of the bonding film on which the embossing is formed may be 30 um or more and 90 um or less.
[0116] The bonding film may be a single-layer film or a laminated film of two or more layers.
[0117] The bonding film may contain a polyvinyl acetal resin.
[0118] The bonding film may include a sound insulating layer.
[0119] A light-transmitting laminate according to another embodiment of the implementation example includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film.
[0120] The bonding film includes a surface on which embossing having a regular or irregular pattern is formed.
[0121] The surface formed with the embossing has Mr1 value and Mr2 value.
[0122] The rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0123] The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value.
[0124] The bonding film includes a region of increased thickness.
[0125] The increased thickness region has two ends, ie, one end and the other end, and thicknesses of the two ends are different from each other.
[0126] Regarding the light-transmitting laminated body, the total number of bubbles generated in three light-transmitting laminated bodies having a width of 300 mm and a length of 300 mm may be 5 or less.
[0127] Any one selected from the group consisting of the first light-transmitting layer, the second light-transmitting layer, and a combination thereof may be aged glass.
[0128] A mobile device according to yet another embodiment of the implementation example includes the light-transmitting laminate.
[0129] In order to achieve the above object, a bonding film of an embodiment disclosed in the present specification includes: a surface having an embossed pattern with a regular pattern or an irregular pattern; the surface having the embossed pattern has an Mr1 value and an Mr2 value, the rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%, the Mr1 value of the surface having the embossed pattern is equal to or greater than the rev_Mr2 value, and the peak-to-valley distribution value is denoted by Spv, which is represented by the following formula 1, the peak-to-valley distribution value of the surface having the embossed pattern is greater than or equal to 0% and less than or equal to 25%,
[0130] Formula 1:
[0131] Spv=Mr1-rev_Mr2
[0132] In the first formula, Spv is the peak-to-valley distribution value, and rev_Mr2 is the value obtained by subtracting Mr2 from 100%.
[0133] The Mr1 value is 10% or more.
[0134] In order to achieve the above object, a light-transmitting laminate of an embodiment disclosed in the present specification includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film, wherein the bonding film includes a surface formed with an embossing having a regular pattern or an irregular pattern; the surface formed with the embossing has an Mr1 value and an Mr2 value, the rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%, the Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value, and assuming that the peak-to-valley distribution value is Spv, it is expressed by the following formula 1, the peak-to-valley distribution value of the surface formed with the embossing is greater than 0% and less than 25%,
[0135] Formula 1:
[0136] Spv=Mr1-rev_Mr2
[0137] In the first formula, Spv is the peak-to-valley distribution value, and rev_Mr2 is the value obtained by subtracting Mr2 from 100%.
[0138] The Mr1 value is 10% or more.
[0139] Effects of the Invention
[0140] The bonding film of the implementation example and the light-transmitting laminate including the same can improve the degassing stability and edge sealing characteristics when forming the light-transmitting laminate by controlling the characteristics of the embossed surface, and can provide a bonding film that can suppress the occurrence of ghosting in the bonded glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0141] Figure 1 and Figure 2 Each of them is a cross-sectional view schematically showing a bonding film according to an implementation example.
[0142] Figure 3 a), b), and c) are cross-sectional views schematically showing different implementation examples of bonding films including a sound insulation layer.
[0143] Figure 4 This is a conceptual diagram for explaining an embossing roll used in the process of preparing a bonding film of a comparative example.
[0144] Figure 5 This is a conceptual diagram for explaining a process of forming surface embossing in a process of preparing a bonding film prepared in one embodiment.
[0145] Description of Reference Numerals
[0146] 100: Bonding film
[0147] 500, 500': Embossing roller
[0148] 10, 11: Bonding layer
[0149] 20: Sound insulation layer
[0150] A: Area of increased thickness. DETAILED DESCRIPTION
[0151] Below, the embodiments are described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the embodiments. However, the present invention can be implemented in various forms and is not limited to the embodiments described in this specification. In this specification, similar parts are given the same reference numerals.
[0152] The terms "approximately" or "substantially" etc. used in this specification to express degree are used to express numerical values or values close to them when there are inherent manufacturing and material tolerances in the meaning involved, and are intended to prevent the accurate or absolute numerical values disclosed in the examples from being used improperly or illegally by any unreasonable third party for understanding.
[0153] Throughout the specification, "a combination thereof" as a term included in a Markush-type description means a mixture or combination of one or more selected from the group consisting of a plurality of components of the Markush-type description, thereby indicating that one or more selected from the group consisting of the plurality of components is included.
[0154] Throughout the specification, the description of "A and / or B" means "A, B, or A and B".
[0155] Throughout the specification, unless otherwise specified, terms such as "first," "second," or "A," "B," etc. are used to distinguish the same terms from one another.
[0156] In this specification, "B is located on A" means that B is located on A in direct contact with A, or that B is located on A with other layers sandwiched between A and B, and is not limited to the meaning that B is located on A in direct contact with the surface of A.
[0157] In the present specification, unless otherwise specified, an expression in the singular may be construed as including the meaning of the singular or the plural as read in the context.
[0158] In this specification, the size of each component in the drawings may be exaggeratedly shown for the purpose of explanation of the invention and may be different from an actually applicable size.
[0159] In the present specification, the content of the hydroxyl group is evaluated by measuring the amount of ethylene groups to which the hydroxyl groups of the above-mentioned polyvinyl acetal resin are bonded according to the method of JIS K6728.
[0160] In this specification, A1, A2, Mr1, Mr2, Sk, Spk, Svk, and Sz are evaluated according to ISO_25178.
[0161] A1, A2, Mr1, Mr2, Sk, Spk, Svk and S*vk are values derived from a support length ratio curve (areal material ratio curve, Abbott-Firestone curve) graph and can be measured using a three-dimensional roughness measuring instrument.
[0162] The support length ratio curve is a curve obtained by mathematically converting the surface profile height of an object into a cumulative probability density function, and is one of the methods for expressing the surface characteristics of an object.
[0163] The equivalent straight line is used for the support length ratio curve. The equivalent straight line is a straight line that includes 40% of the measurement points of the curve. It refers to a straight line with the smallest slope when connecting the two end points of an interval of 40% of the interval set arbitrarily in the overall interval of the support length ratio (Areal material ratio, X-axis) of the curve. The values representing surface characteristics such as A1, A2, Mr1, Mr2, Sk, Spk, Svk and S*vk values can be derived from the equivalent straight line.
[0164] The bonding film is given surface embossing properties such as a concave-convex pattern or melt fracture to prevent unnecessary bonding between the surfaces when it is wound, and to have degassing properties when it is bonded to a light-transmitting body such as a glass plate. However, if only the degassing property is emphasized, it may lead to a decrease in optical properties or insufficient edge sealing properties, and if the edge sealing properties are emphasized, it may cause problems such as the occurrence of bubbles, thereby reducing optical properties.
[0165] Pre-bonding is usually performed at a lower temperature than the main bonding. Compared with the pre-bonding process using a vacuum ring, the actual temperature of the glass in the process using a nip roll is relatively lower. Usually, pre-bonding is performed at a temperature below about 70°C based on the temperature of the glass surface.
[0166] When pre-bonding is performed at low temperature, in order to obtain stable bonding performance, the roughness of the embossed pattern is usually simply reduced to ensure processability, but this is also one of the reasons for the reduction of deairing performance.
[0167] On the other hand, the bonding film can be bonded to a light-transmitting body such as a glass plate to form a light-transmitting laminate. A head-up display can be provided to the user (driver) by projecting an image onto the light-transmitting laminate. However, the image projected onto the light-transmitting laminate may pass through the light-transmitting body such as glass and the bonding film or be reflected to form a double image, which may be perceived by the user as a double image or reduce the clarity of the image. In order to suppress this phenomenon, a wedge-shaped bonding film or the like is applied to a head-up display.
[0168] The inventors of the implementation example discovered that the two complementary characteristics of degassing performance and edge sealing can be simultaneously satisfied by controlling the A1, A2, Mr1, Mr2, Svk, S*vk characteristics, etc. of the embossed surface, and that the formation of ghosting of the head-up display image can be suppressed by adjusting the wedge angle of the bonding film during the formation of a light-transmitting laminate such as bonded glass, thereby completing the implementation example.
[0169] The following describes an implementation example in more detail.
[0170] A1, A2, Mr1, Mr2, Sz, Sk, Spk and Svk are evaluated according to ISO_25178.
[0171] A1, A2, Mr1, Mr2, Sk, Spk, Svk and S*vk values can be derived from the support length ratio curve (areal material ratio curve, Abbott-Firestone curve). The A1, A2, Mr1, Mr2, Sk, Spk, Svk and S*vk values can be obtained by measuring and calculating using a three-dimensional roughness measuring instrument.
[0172] The three-dimensional roughness can be measured by 2 Specifically, when using a 3D optical profilometer or a 3D laser measuring microscope to measure, the 340,000 μm at different locations is used. 2 The above area is measured more than 5 times, and the average value except the highest and lowest values is calculated. The average value can be used as the 3D roughness measurement value. When using a 3D laser measuring microscope, the stitching function is used to stitch images of adjacent positions to measure the 3D roughness. The 3D roughness measurement using the stitching function can also be performed at 1,000,000μm. 2 The average value of the values measured in the above total area was evaluated.
[0173] For example, the three-dimensional roughness can be measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) produced by Bruker Corporation through a vertical scanning interferometry mode.
[0174] In order to achieve the above object, a bonding film according to an embodiment of the present specification includes a surface having embossed patterns, and an A2 / A1 value of the surface having embossed patterns is 1 or less.
[0175] The bonding film includes a surface with an embossed surface, and the A2 / A1 value of the embossed surface can be less than 1, preferably less than 0.85, and can be greater than 0.02, preferably greater than 0.05. When the A2 / A1 value of the embossed surface is less than 1, it is substantially possible to improve the edge sealing while maintaining the degassing stability at or above the same level. In addition, when the A2 / A1 value of the embossed surface is within the above range, even at a relatively low temperature, the edge sealing properties can be substantially improved without changing the roughness by appropriately adjusting the volume density of the upper and lower portions of the embossed surface.
[0176] In the bonding film, the A1 value of the surface on which the embossing is formed may be 0.5 or more, preferably 0.6 or more, and may be 3 or less, preferably 2 or less. When the A1 value is 0.5 or more, the peak of the surface on which the embossing is formed can be controlled to maintain a volume above a certain level, and the degassing performance and the edge sealing performance can be further improved.
[0177] In the bonding film, the A2 value of the surface with the embossing may be 0.6 or less, preferably 0.5 or less, and may be 0.05 or more, preferably 0.1 or more. When the A2 value is 0.6 or less, the pore volume of the valley of the bonding film surface pattern is small, so the degassing amount can be adjusted below an appropriate level and the degassing stability can be optimized.
[0178] The Sz value of the surface of the bonding film on which the embossing is formed may be 30 to 90 μm.
[0179] The Sz value is a value evaluated according to ISO_25178, and refers to the sum of the maximum peak height value and the maximum valley depth value, and refers to the height difference between the peak and the valley.
[0180] The Sz value can be obtained by measuring and calculating using a three-dimensional roughness measuring instrument, for example, by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) from Bruker to measure the three-dimensional roughness in a vertical scanning interference mode.
[0181] The Sz value of the surface of the bonding film on which the embossing is formed may be 30 to 90 μm, 40 to 80 μm, or 45 to 75 μm. The bonding film having such a surface roughness may have relatively excellent degassing stability.
[0182] The bonding film having the above-described Sz value of the surface having the embossed pattern and the above-described A2 / A1 value has excellent degassing stability even when pre-bonding is performed at a low temperature and can further improve edge sealing properties.
[0183] In order to achieve the above object, a bonding film according to another embodiment disclosed in the present specification includes a surface on which embossing having a regular or irregular pattern is formed.
[0184] The surface formed with the embossing has Mr1 value and Mr2 value.
[0185] The rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0186] The Mr1 value of the surface formed with the embossing may be greater than or equal to the rev_Mr2 value.
[0187] When the Mr1 value is greater than or equal to the rev_Mr2 value, the volume density of protruding peaks and the volume density of protruding valleys are adjusted to appropriate levels, thereby substantially improving edge sealing while maintaining degassing stability at or above the same level.
[0188] The bonding film has a peak-to-valley distribution value (Spv). The peak-to-valley distribution value is represented by the following formula 1.
[0189] Formula 1:
[0190] Spv=Mr1-rev_Mr2
[0191] In the first formula, the Spv is a peak-to-valley distribution value, and the rev_Mr2 value is a value obtained by subtracting the Mr2 value from 100%.
[0192] The peak-to-valley distribution value of the embossed surface may be 0% to 25%, or 1% to 15%. When the peak-to-valley distribution value is 0% to 25%, the volume density of the protruding valley of the valley portion is controlled to be relatively low, thereby further improving the low-temperature edge sealing performance.
[0193] In the bonding film, the Mr1 value of the surface with embossing may be 10% or more, preferably 12% or more, and may be 40% or less, preferably 38% or less. When the Mr1 value is 10% or more, the edge sealing property can be further improved by maintaining the volume density of the protruding peaks constituting the pattern protrusions in the surface with embossing above a certain density.
[0194] In order to achieve the above object, a bonding film according to another embodiment disclosed in the present specification includes a surface having an embossed pattern with a regular or irregular pattern. The DSvk value of the embossed surface represented by the following formula 2 is 6 um or less. The bonding film may contain 24 to 40 wt % of a plasticizer based on the entire bonding film.
[0195] Formula 2:
[0196] DSvk=S*vk–Svk
[0197] In the second formula, the Svk value is a value evaluated according to ISO_25178, and the S*vk value is a height value of a point having a support length ratio Mr2 in a support length ratio curve according to ISO_25178.
[0198] The DSvk value of the surface formed with the embossing may be 6 um or less. The DSvk value may be 5 um or less. The DSvk value may be 4 um or less. The DSvk value may be 1 um or more. The DSvk value may be 1.5 um or more. In this case, the generation of valleys that are too deep compared to the average depth of the convex valleys can be suppressed, thereby improving the bonding property of the bonding film.
[0199] The ratio of the Svk value to the DSvk value of the surface on which the embossing is formed may be 0.1 or more and 1.5 or less. The ratio is calculated by dividing the Svk value by the DSvk value.
[0200] The ratio of the Svk value to the DSvk value may be greater than 0.1. The ratio of the Svk value to the DSvk value may be greater than 0.2. The ratio of the Svk value to the DSvk value may be less than 1.5. The ratio of the Svk value to the DSvk value may be less than 1.2. In this case, the valley depth of the surface formed with the embossing is adjusted to be distributed within a certain range, so that when bonding is performed at a low temperature, the pattern including the valley can collapse smoothly.
[0201] The A2 value of the surface on which the embossing is formed may be 0.16 or more and 0.5 or less.
[0202] The A2 value of the surface formed with the embossing may be less than 0.5. The A2 value may be less than 0.3. The A2 value may be greater than 0.16. The A2 value may be greater than 0.18. In this case, the volume density of the valleys included in the surface formed with the embossing is adjusted so that when the bonding film is bonded to the light-transmitting body, the air remaining between the light-transmitting body and the bonding film can be smoothly discharged, and when bonding is performed at a low temperature, the pattern can be smoothly collapsed, thereby improving the edge sealing of the bonding film.
[0203] The Svk value of the surface formed with the embossing may be 4 to 10 um. The Svk value may be 4 um or more. The Svk value may be 5 um or more. The Svk value may be 10 um or less. The Svk value may be 8 um or less. In this case, the depth distribution of the valley that plays a degassing role during bonding is adjusted, so that the degassing property of the bonding film can be improved, and even after the bonding process at low temperature, no pattern can be observed on the surface of the light-transmitting laminate.
[0204] The S*vk value of the surface with the embossing may be less than 12 um. The S*vk value may be less than 11 um. The S*vk value may be greater than 3 um. The S*vk value may be greater than 5 um. In this case, the formation of valleys with excessive depth is suppressed, and most of the pattern collapses when the bonding film is pre-bonded with the light-transmitting body, so that the optical properties of the light-transmitting laminate after the bonding process can be improved.
[0205] The DSvk / Sz value of the surface formed with the embossing may be 0.01 to 0.08.
[0206] The Sz value is a value evaluated according to ISO 25178. The Sz value can be obtained by measuring and calculating using a three-dimensional roughness measuring instrument. The three-dimensional roughness measuring method is as described above.
[0207] The DSvk / Sz value of the surface formed with the embossing may be 0.01 or more. The DSvk / Sz value may be 0.03 or more. The DSvk / Sz value may be 0.08 or less. The DSvk / Sz value may be 0.06 or less. In this case, the depth distribution of the valley is adjusted relative to the surface roughness (Sz value), so that when bonding is performed at low temperatures, even if the surface roughness of the surface formed with the embossing is not reduced, a bonding film with stable edge sealing can be provided.
[0208] The surface formed with the embossing may include fine concavities and convexities.
[0209] The fine concavoconvexities may be formed at the peaks of the embossed pattern or at the valleys of the embossed pattern.
[0210] In the process of forming embossing, a method of further forming a fine pattern on one surface of the bonding film, or a method of further forming a fine pattern on the surface of a mold or roller for transferring embossing, can be adopted to make the surface formed with embossing have the characteristics as described above. Specifically, the fine pattern can be included on the surface of the bonding film by the following method: further forming a fine pattern on a mold or roller for transferring embossing to the bonding film, and using a mold or roller to transfer the pattern to the surface of the bonding film. For example, the fine pattern can be further formed by precision sandblasting the mold or roller. However, the method of further forming a fine pattern is not limited to this.
[0211] Figure 1 and Figure 2 are schematic cross-sectional views of a bonding film according to an embodiment, Figure 3 In a), b) and c), cross-sectional views of bonding films including sound insulation layers in different embodiments are schematically shown. Figures 1 to 3 The embodiments are described in more detail.
[0212] The bonding film 100 includes a surface on which the embossing is formed, and the value of A2 / A1 of the surface on which the embossing is formed is 1 or less and includes a thickness-increased region A.
[0213] The increased thickness region A has two ends, ie, one end and the other end, when viewed in cross section, and thicknesses of the two ends are different from each other.
[0214] The thickness of the thickness-increased region A may increase from the one end to the other end. The thickness may increase at a certain ratio over the entire thickness-increased region A. The thickness may increase at a gradually increasing ratio over the entire thickness-increased region A. The increase in thickness may increase at a gradually decreasing ratio over the entire thickness-increased region A.
[0215] The thickness of the thickness-increased region A may decrease from the one end to the other end. The thickness may decrease at a certain ratio over the entire thickness-increased region A. The thickness may decrease at a gradually increasing ratio over the entire thickness-increased region A. The increase in thickness may decrease at a gradually decreasing ratio over the entire thickness-increased region A.
[0216] The path of the transmitted light or the angle of the reflected light can be adjusted by making the thicknesses of the two ends of the thickness increased region A different from each other, so that no double image is formed when light is irradiated from the light source of the head-up display system to the light-transmitting laminate.
[0217] The increased thickness region A has a wedge angle (θ), and the wedge angle (θ) is expressed by the following formula 3. In the increased thickness region A, the wedge angle may be greater than or equal to 0.01° and less than or equal to 0.04°.
[0218] Form 3:
[0219]
[0220] In the third formula, Hb is the thickness of the thicker one of the two ends of the thickness-increased region A, and Ha is the thickness of the thinner one of the two ends of the thickness-increased region A.
[0221] The w is the width between the two ends of the thickness-increased region A.
[0222] The Hb value and the Ha value may be measured using a Japanese Mitutoyo 547-401 thickness gauge, but the present invention is not limited thereto.
[0223] The wedge angle of the thickness increased region A may be 0.01° or more. The wedge angle of the thickness increased region A may be 0.04° or less. The wedge angle of the thickness increased region A may be 0.011° or more. The wedge angle of the thickness increased region A may be 0.03° or less. When the bonding film having such a wedge angle is used as an intermediate film for a head-up display, the formation of ghosting can be effectively suppressed.
[0224] The ratio of the Hb to the w may be greater than or equal to 0.001 and less than or equal to 0.002.
[0225] The ratio of Ha to w may be greater than or equal to 0.0002 and less than or equal to 0.0015.
[0226] The specific measurement methods of the Ha value and the Hb value are as described above.
[0227] Specifically, the Ha value may be 0.38 mm or more. Alternatively, the Ha value may be 0.40 mm or more. When the Ha value is 0.38 mm or more, the bonding film may have stable penetration resistance.
[0228] The ratio of Hb to w may be greater than 0.001 and less than 0.002. In addition, the ratio of Hb to w may be greater than 0.001 and less than 0.0018. When the ratio of w to Hb is within the above range, a bonding film having excellent impact resistance and penetration resistance and having a ghosting prevention function can be provided.
[0229] The ratio of Ha to w may be 0.0002 or more and 0.0015 or less. In addition, the ratio of Ha to w may be 0.0003 or more and 0.0013 or less. When the ratio of Ha to w is within the above range, a bonding film having both penetration resistance and ghosting prevention function can be provided.
[0230] The increased thickness region A may be located in a part or the entirety of the bonding film 100 .
[0231] When the increased thickness region A is located at a portion of the bonding film 100 , the increased thickness region A may be located at an edge of the bonding film 100 .
[0232] The bonding film 100 may include one or more increased thickness regions A.
[0233] The bonding film 100 includes a surface formed with embossing having a regular or irregular pattern. The surface formed with embossing has Mr1 value and Mr2 value, rev_Mr2 value is a value obtained by subtracting Mr2 value from 100%, and the Mr1 value of the surface formed with embossing is equal to or greater than rev_Mr2 value. The bonding film 100 includes a thickness increased region A.
[0234] The thickness increased region A overlaps with the above content and is therefore omitted.
[0235] The bonding film 100 may be a single-layer film or a multi-layer film.
[0236] The bonding film 100 may include a polyvinyl acetal resin, or may include a polyvinyl acetal resin and a plasticizer.
[0237] Specifically, the content of the polyvinyl acetal resin in the bonding film may be 60 to 76 wt %, 70 to 76 wt %, or 71 to 74 wt %. When the polyvinyl acetal resin is included within such a range, relatively high tensile strength and modulus may be imparted to the bonding laminate film.
[0238] The acetyl content of the polyvinyl acetal resin may be less than 2% by weight, specifically, 0.01 or more and less than 1.5% by weight. The hydroxyl content of the polyvinyl acetal resin may be greater than 15% by weight, greater than 16% by weight, or greater than 19% by weight. In addition, the hydroxyl content of the polyvinyl acetal resin may be less than 30% by weight.
[0239] When the polyvinyl acetal resin having the above-mentioned properties is applied to the bonding film, the bonding film can be excellently bonded to a substrate such as glass and can also have appropriate mechanical properties such as penetration resistance.
[0240] The polyvinyl acetal resin may be obtained by acetalizing polyvinyl alcohol having a degree of polymerization of 1,600 to 3,000 with an aldehyde, or may be obtained by acetalizing polyvinyl alcohol having a degree of polymerization of 1,700 to 2,500 with an aldehyde. When the polyvinyl acetal resin is used, mechanical properties such as penetration resistance can be sufficiently improved.
[0241] The polyvinyl acetal resin may be obtained by synthesizing polyvinyl alcohol and aldehyde, and the type of the aldehyde is not limited. Specifically, the aldehyde may be any one selected from the group consisting of n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, and mixed resins thereof. When n-butyraldehyde is used as the aldehyde, the prepared polyvinyl acetal resin has a refractive index characteristic with a small refractive index difference with glass, and also has a characteristic of excellent bonding strength with glass and the like.
[0242] The content of the plasticizer in the bonding film may be 24 to 40 wt %, 24 to 30 wt %, or 26 to 29 wt %. When the plasticizer is contained within the above range, appropriate bonding strength and impact resistance can be imparted to the bonding laminated film, which is preferred.
[0243] Specifically, the plasticizer can be any one selected from the group consisting of triethylene glycol di-2-ethylhexanoate (3G8), tetraethylene glycol diheptanoate (4G7), triethylene glycol di-2-ethylbutyrate (3GH), triethylene glycol di-2-heptanoate (3G7), dibutoxyethoxyethyl adipate (DBEA), butyl carbitol adipate (DBEEA), dibutyl sebacate (DBS), di-2-hexyl adipate (DHA) and a combination thereof. Specifically, it can include any one selected from the group consisting of triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol di-n-heptanoate and a combination thereof. More specifically, triethylene glycol di-2-ethylhexanoate (3G8) can be used.
[0244] The bonding film may further contain an additive as needed. For example, the additive may be any one selected from the group consisting of an antioxidant, a heat stabilizer, a UV absorber, a UV stabilizer, an IR absorber, a glass bonding strength regulator, and a combination thereof.
[0245] The antioxidant may be a hindered amine or hindered phenol antioxidant. Specifically, in the preparation process of polyvinyl butyral (PVB) requiring a process temperature of 150°C or above, a hindered phenol antioxidant is more preferred. As a hindered phenol antioxidant, for example, IRGANOX 1076, 1010, etc. of BASF can be used.
[0246] Considering the compatibility with the antioxidant, the heat stabilizer may be a phosphite heat stabilizer, for example, IRGAFOS168 from BASF may be used.
[0247] As UV absorbers, Chemisorb 12, Chemisorb 79, Chemisorb 74, Chemisorb 102 from Chemipro Chemical Co., Ltd. and Tinuvin 328, Tinuvin 329, Tinuvin 326 from BASF can be used. As UV stabilizers, Tinuvin from BASF can be used. As the IR absorber, ITO, ATO, AZO, etc. can be used. As glass bonding strength regulators, metal salts of Mg, K, Na, etc., epoxy-modified silicone oils, or mixtures thereof can be used, but are not limited thereto.
[0248] The bonding film 100 may be a multilayer film. The bonding film 100 may be a laminate of more than 2 layers, a laminate of more than 3 layers, or a laminate of more than 5 layers. The multilayer film may include: bonding layers 10 and 11, which are in direct contact with a light-transmitting laminate such as a glass plate; and a core layer (not shown), which is separate from the bonding layers 10 and 11. The core layer may have functionality, for example, it may have a function such as a heat insulation functional layer.
[0249] In the multilayer film, at least one of the bonding layers 10 and 11 may contain a polyvinyl acetal resin as the composition of the single layer film as described above, or may contain a polyvinyl acetal resin and a plasticizer. The description of the polyvinyl acetal resin and the plasticizer overlaps with the above description and is therefore omitted.
[0250] The bonding film 100 may include a sound insulation layer 20. The sound insulation layer 20 may be located between the bonding layers 10 and 11, or may be located on one surface of the bonding layer 10.
[0251] The sound insulation layer 20 may include polyvinyl acetal resin.
[0252] The content of the polyvinyl acetal resin in the sound insulation layer 20 may be 54 wt % or more and 76 wt % or less, or 60 wt % or more and 70 wt % or less.
[0253] The content of the plasticizer in the sound insulation layer 20 may be greater than or equal to 24 wt % and less than or equal to 46 wt %, or greater than or equal to 30 wt % and less than or equal to 40 wt %.
[0254] The acetyl content of the polyvinyl acetal resin contained in the sound insulation layer 20 may be 8% by weight or more, specifically, 8% by weight or more and 30% by weight or less, based on the entire polyvinyl acetal resin. In addition, the hydroxyl content of the polyvinyl acetal resin contained in the sound insulation layer 20 may be 26% by weight or less, and 5% by weight or more and 25% by weight or less. In this case, a more stable sound insulation property can be imparted to the bonding film 100.
[0255] The bonding film 100 can be prepared into a sheet by extruding a bonding film preparation composition containing a resin and a plasticizer and, if necessary, an additive, and then molding it through a T-die (T-DIE) etc. When the bonding film is a multilayer film, a laminating unit such as a feed block etc. can be further applied to the front end of the T-DIE.
[0256] The bonding film 100 formed in a sheet shape may be prepared into a bonding film through processes such as thickness control and embossing, but the method for preparing the bonding film is not limited thereto.
[0257] When the bonding film 100 has both the characteristics of the surface on which the embossing is formed and the characteristics of the increased thickness region A as described above, it is possible to have both the surface bonding characteristics and the ghosting prevention function.
[0258] In particular, when the thickness increased region A is partially present in the bonding film 100, a curved portion where the surface angle of the bonding film changes sharply is generated, and bubbles are easily generated in the curved portion when matched with a light-transmitting body such as a glass plate. However, a bonding film having the characteristics of the implementation example can provide a bonding film including the curved portion, in which the generation of bubbles is controlled as a whole, and a bonding film having excellent optical properties and an excellent ghosting prevention function can be provided.
[0259] Figure 4 This is a conceptual diagram for explaining an embossing roller used in the preparation process of a bonding film of a comparative example. Figure 5 This is a conceptual diagram for explaining the process of forming surface embossing in the preparation process of the bonding film prepared in one embodiment. Figure 4 and Figure 5 A method for producing a bonding film having surface embossing according to a realization example will be described.
[0260] The bonding film 100 is prepared by forming a single-layer film or a multi-layer film into a sheet by the above-mentioned method, and then forming embossments on the surface of the film using an embossing roll 500 or a mold (not shown).
[0261] The surface characteristics of the embossing roller 500 or the mold are transferred to the surface of the monolayer film or the multilayer film by the heating and pressing method generally applied to the bonding film 100. In this case, the transfer rate may be 0.6 or more, 0.7 or more, or 0.99 or less. The transfer rate is evaluated as the surface roughness of the corresponding film surface when the surface roughness of the embossing is regarded as 1.
[0262] The surface properties of the embossing roller 500 or the mold can be transferred to the surface of a single-layer film or a multi-layer film by a heating and pressurizing method commonly used for bonding films. Therefore, the properties of the embossed surface of the film can be controlled by controlling the surface properties of the embossing roller or the mold.
[0263] The embossing roller 500 or the mold can be formed by Figure 4 The basic roller or mold shown (applied in Comparative Example 1) is prepared by sandblasting the concave part and grinding the convex part. At this time, the surface characteristics can be controlled by adjusting the conditions used in the sandblasting (particle size, spray pressure, spray distance, spray angle, etc.) and the conditions used in the grinding treatment (grinding degree), which is reflected in the embossed characteristics on the film surface in a complementary manner.
[0264] For example, the concave portion of the basic roller having a matte pattern with an Rz roughness value of 30 to 90 μm can be subjected to sandblasting treatment 1 to 10 times at a distance of 40 to 45 cm, with a spray pressure of 0.3 to 0.5 MPa, and a nozzle angle of 85 to 105 degrees, by direct pressure spraying particles with an average outer diameter of 3 to 8 μm. Through the sandblasting treatment of the concave portion, a fine pattern is formed on the convex portion of the film surface in a complementary manner, so that the volume of the convex portion on the film surface can be relatively increased.
[0265] In addition, the convex portion of the basic roller can be ground, and the grinding thickness can be 1 to 5 um, preferably, the grinding thickness can be 1 to 3 um. The pores between the concave portions on the film surface can be reduced in a complementary manner by grinding the convex portion, and the degassing stability can be further improved.
[0266] The sandblasting process and the grinding process may be repeated 1 to 10 times.
[0267] As another example, the concave portion of the basic roller having a matte pattern with an Rz roughness value of 30 to 90 μm can be subjected to sandblasting treatment 1 to 10 times at a distance of 15 to 20 cm, with a spray pressure of 0.3 to 0.5 MPa, and a nozzle angle of 85 to 105 degrees, by direct pressure spraying particles with an average outer diameter of 3 to 8 μm. Through the sandblasting treatment of the concave portion, a fine pattern is formed on the convex portion of the film surface in a complementary manner, so the volume of the convex portion on the film surface can be relatively increased.
[0268] In addition, the convex portion of the basic roller can be ground, and the grinding thickness can be 1 to 10 um, preferably, the grinding thickness can be 3 to 5 um. The pores between the concave portions on the film surface can be reduced in a complementary manner by grinding the convex portion, and the degassing stability can be further improved.
[0269] The sandblasting treatment and the grinding treatment may be repeated 1 to 10 times.
[0270] As another example, the surface of a basic mold or roller having a matte pattern with an Rz roughness value of 30 to 90 μm can be shot peened once at a distance of 15 to 20 cm, with a spray pressure of 0.4 MPa and a nozzle angle of 90°, with particles having an average outer diameter of 50 μm being sprayed in a direct pressure manner. Through the shot peening, a fine pattern is formed on the film surface in a complementary manner, so that the depth distribution of the valleys on the film surface can be adjusted.
[0271] In addition, the surface of the base mold or the roller may be subjected to sandblasting treatment 1 to 10 times, where particles with an average outer diameter of 5 μm are sprayed at a distance of 15 to 20 cm, a spray pressure of 0.4 MPa, and a nozzle angle of 5 to 10 degrees by direct pressure. The bonding force of the bonding film can be improved by etching the excessively protruding portions in the pattern on the film surface in a complementary manner through sandblasting.
[0272] A light-transmitting laminated body according to another embodiment disclosed in the present specification includes: a first light-transmitting layer; a bonding film located on one surface of the first light-transmitting layer; and a second light-transmitting layer located on the bonding film.
[0273] The first light-transmitting layer and the second light-transmitting layer can each independently be light-transmitting glass or light-transmitting plastic.
[0274] The bonding film is the bonding film described above, and the specific description thereof overlaps with the above description and is therefore omitted.
[0275] In the light-transmitting laminate, the total number of bubbles generated in three light-transmitting laminates with a width of 300 mm and a length of 300 mm may be 5 or less. The specific description of the bubble number measurement conditions and measurement method of the light-transmitting laminate overlaps with the description in the following evaluation examples and is therefore omitted.
[0276] In the light-transmitting laminate, any one selected from the group consisting of the first light-transmitting layer, the second light-transmitting layer, and a combination thereof may be weathered glass.
[0277] In the case of ordinary glass, due to the influence of ambient temperature and humidity, scale appears on the surface over time, so that the edge sealing performance decreases as the flatness decreases. Specifically, it can be confirmed whether the bonding film has excellent edge sealing properties under harsh conditions by using glass that has been aged at a specific temperature and relative humidity for a specified period as a light-transmitting layer (first light-transmitting layer or second light-transmitting layer), thereby inducing the formation of scale on the surface and then applying it to the preparation of a light-transmitting laminate.
[0278] The aging treatment may be performed by placing the glass under conditions of 25° C. and 40% relative humidity for 60 days.
[0279] Even when the aging-treated glass is used, the light-transmitting laminate has excellent edge sealing properties. This is considered to be because the surface properties of the bonding film of the implementation example are controlled, thereby achieving excellent effects.
[0280] A mobile device of another embodiment disclosed in the present specification includes the light-transmitting laminate described above. The mobile device includes: a main body forming the main body of the mobile device; a driving part (engine, etc.) mounted on the main body; a driving wheel (wheel, etc.) rotatably mounted on the main body; a connecting device connecting the driving wheel and the driving part; and a windshield, which is a light-transmitting laminate mounted on a part of the main body to block wind from the outside.
[0281] In the following description of the experiment, when the unit of "%" is unclear, if it is unclear whether "%" means weight % or mole % the unit is weight %.
[0282] Preparation Example 1: Roller Processing
[0283] A steel roller having an embossed shape with a matte pattern in which dots are randomly formed is further provided with a fine pattern in the recessed portions, and a grinding treatment is performed on the raised portions.
[0284] like Figure 4 As shown, a roller having irregular concavoconvexities in a matte pattern morphology (Rz=50 um) was used as ROLL 0.
[0285] For the same roller as ROLL 0, ROLL 1a, ROLL 1b, and ROLL 1c were prepared by sandblasting the valleys and then grinding the peaks. Specifically, the valleys of the matte pattern were sandblasted, and the peaks of the matte pattern were ground. The sandblasting was performed by directly spraying particles with an average outer diameter of 5 μm through a 200-mesh foreign matter removal filter at a distance of 40 to 45 cm at a spray pressure of 0.4 MPa. The angle between the mold surface and the sprayed particles (or nozzle) was 85 to 105 degrees.
[0286] Roll 1a was subjected to the above-mentioned sandblasting and grinding process once, Roll 1b was subjected to the above-mentioned sandblasting and grinding process three times, and Roll 1c was subjected to the above-mentioned sandblasting and grinding process ten times.
[0287] As shown in Table 1 below, the roller prepared by the above process was applied to Examples or Comparative Examples.
[0288] Preparation Example 1: Preparation of membrane
[0289] The respective components used in the following Examples and Comparative Examples are as follows.
[0290] Polyvinyl butyral resin (A1): Polyvinyl alcohol (PVA) with a polymerization degree of 1700 and a saponification degree of 99 and n-BAL were added, and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 20.3wt% of hydroxyl groups, 78.9wt% of butyral groups, and 0.8wt% of acetyl groups.
[0291] Preparation of additives: 0.1 wt% of Irganox 1076 as an antioxidant, 0.2 wt% of TINUVIN-328 as a UV absorber, and 0.03 wt% of magnesium acetate (Mg Acetate) as a bonding strength regulator were mixed and stirred in a rotating cup to be fully dispersed (total 0.33 wt%).
[0292] Examples 1 to 3: 72.67 wt% of polyvinyl butyral resin (A1), 27 wt% of 3g8 as a plasticizer, and 0.33 wt% of an additive were put into a twin-screw extruder (a) and extruded, and then formed into a film through a T-die (T-DIE). Before winding, different rolls (ROLL 1a, ROLL 1b, ROLL 1c) were used for embossing treatment, as shown in Table 1 below, and the film with the surface pattern transferred was sampled in the form of a roll sample, thereby preparing the films of Examples 1 to 3. The prepared film had a thickness of 760 um and a width of 1.0 M.
[0293] Comparative Example 1: A film of Comparative Example 1 was prepared in the same manner as in Examples 1 to 3 except that the embossing treatment was performed using a roll (ROLL 0) that was not subjected to fine pattern processing of projections and depressions.
[0294] Evaluation Example 1: Evaluation of physical properties
[0295] Surface roughness measurement
[0296] The A1 value and the A2 value were respectively obtained by using an apparatus for measuring three-dimensional roughness according to ISO_25178. Specifically, the three-dimensional roughness was measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) manufactured by Bruker in a vertical scanning interferometric mode.
[0297] Specifically, the measurement was performed using a 2x eyepiece and a 5x objective lens, and at this time, the area of 0 to 0.887 mm on the x-axis and 0 to 0.670 mm on the y-axis could be scanned. Under the same pattern, the measurement area was randomly determined, and the measurement was repeated 5 times, and the average of the 3 measured values excluding the maximum and minimum values was taken.
[0298] Sz, A1 (peak region), A2 (valley region), and A2 / A1 values as measurement results are shown in Table 1 below.
[0299] Edge Seal Evaluation:
[0300] Preparation of samples for evaluation 1): The films of the examples and comparative examples were cut into pieces with a width*length of 1000*1000 mm and then aged by leaving them at 20 degrees and 20 rh% for 2 days. A 300*300 mm test piece was cut based on the center portion in the width direction of the film, and three test pieces were cut in the same manner in the length direction.
[0301] The test piece was placed between two sheets of flat glass having a thickness of 2.1T (T=mm) and pre-bonded. Three evaluation samples were prepared for each of the examples and comparative examples.
[0302] The width and length of a single evaluation sample were 300 mm, respectively, and the total length of the four sides of the edge of one sample was 1200 mm. Three evaluation samples were prepared for each of the examples and comparative examples, and the edge sealing was evaluated over a total of 3.6 m.
[0303] The pre-bonding process was performed by degassing at 20° C. for 5 minutes using a vacuum ring, and then maintaining at three different temperature intervals of 70° C., 85° C., and 100° C. for 15 minutes each.
[0304] Preparation of evaluation samples 2): A flat glass having a thickness of 2.1T was cut into a width*length of 300*300mm and then aged by leaving it at 25°C, 40rh% for 60 days. An evaluation sample was prepared using the aged flat glass in the same manner as in the preparation of the evaluation sample 1), however, the holding temperature after degassing was set to 85°C.
[0305] Evaluation of edge sealing degree): The evaluation samples were evaluated with the naked eye, and when the edge sealing was complete and the pattern was not visible at all, it was evaluated as 5 points, when the edge sealing degree was good and the pattern was faintly visible with the naked eye, it was evaluated as 4 points, when the edge sealing degree was ordinary and the pattern was visible with the naked eye, it was evaluated as 3 points, when the edge sealing degree was poor and the pattern was visible with the naked eye, it was evaluated as 2 points, and when the edge sealing degree was poor and the pattern was obviously visible with the naked eye, it was evaluated as 1 point, and the total score of the 3 samples is shown in the following Table 2.
[0306] Bubble Generation Evaluation
[0307] The evaluation samples of the examples and comparative examples that had completed preliminary bonding were compressed in an autoclave at 140°C and 1.2 MPa for 20 minutes to obtain bonded glasses that had completed main bonding. The time required for main bonding, including the heating time and the cooling time, was 90 minutes in total.
[0308] The number of bubbles generated in the bonding glass after the main bonding was confirmed with the naked eye. When the total number of bubbles confirmed in the three samples of the embodiment and the comparative example was 5 or less, it was marked as 5 points, when the total number of bubbles was 6 to 10, it was marked as 3 points, and when the total number of bubbles was 11 or more, it was marked as 1 point. The results are shown in Table 2.
[0309] [Table 1]
[0310]
[0311] [Table 2]
[0312]
[0313]
[0314] Referring to Table 1, when comparing the Sz values of Examples 1 to 3 and Comparative Example 1, in which the roller surface is subjected to additional processing of a fine pattern by sandblasting and grinding, the maximum difference is only 2.6 μm, and it can be seen that even if a fine pattern is additionally processed on the roller surface, the value of the surface roughness Sz does not change significantly. In addition, in the case of Examples 1 to 3 in which a fine pattern is additionally processed, the A2 / A1 value is measured to be less than 1, while in the case of Comparative Example 1 in which a fine pattern is not additionally processed, the A2 / A1 value is measured to be 3.57, showing a huge difference.
[0315] Referring to Table 2, in the edge sealing evaluation, for the embodiment, scores of 12 or more were obtained under all conditions. On the contrary, for Comparative Example 1, scores of less than 5 were obtained for the sample pre-bonded with ordinary glass at 70°C and the sample pre-bonded with aged glass at 85°C. This shows that when additional processing of fine patterns is performed on the film, the edge sealing of the film can be improved.
[0316] In addition, in the bubble generation evaluation, as for the example, 5 points were obtained under all conditions. On the contrary, in the case of Comparative Example 1, except for the sample pre-bonded with ordinary glass at 100°C, scores below 3 were obtained. This shows that when additional processing of fine patterns is performed on the film, the degassing stability of the film can be improved.
[0317] Preparation Example 2: Roller Processing
[0318] A steel roller having an embossed shape with a matte pattern in which dots are randomly formed is further provided with a fine pattern in the recessed portions, and a grinding treatment is performed on the raised portions.
[0319] like Figure 4 As shown, a roller (Rz=50 μm) having concavoconvexities in a matte pattern was used as ROLL 0.
[0320] For the same roller as ROLL 0, ROLL 2a, ROLL 2b, and ROLL 2c were prepared by sandblasting the valleys and then grinding the peaks. Specifically, the valleys of the matte pattern were sandblasted, and the peaks of the matte pattern were ground. The sandblasting was performed by spraying particles with an average outer diameter of 5um through a 200-mesh foreign matter removal filter at a distance of 15 to 20cm at a spray pressure of 0.4MPa in a direct pressure manner. The angle between the matte pattern surface and the sprayed particles (or nozzle) was 85 to 105 degrees.
[0321] Roll 2a was subjected to the above-mentioned sandblasting and grinding treatment once, Roll 2b was subjected to the above-mentioned sandblasting and grinding treatment twice, and Roll 2c was subjected to the above-mentioned sandblasting and grinding treatment four times.
[0322] As shown in Table 3 below, the roller prepared by the above process was applied to the following Examples or Comparative Examples.
[0323] Preparation Example 2: Preparation of membrane
[0324] The respective components used in the following Examples and Comparative Examples are as follows.
[0325] Polyvinyl butyral resin (A1) : Polyvinyl alcohol (PVA) with a polymerization degree of 1700 and a saponification degree of 99 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 20.3 wt % of hydroxyl groups, 78.9 wt % of butyral groups and 0.8 wt % of acetyl groups.
[0326] Preparation of additives: 0.1 parts by weight of Irganox 1076 as an antioxidant, 0.2 parts by weight of TINUVIN-328 as a UV absorber, and 0.03 parts by weight of magnesium acetate (Mg Acetate) as a bonding strength regulator were mixed and stirred in a rotating cup to be fully dispersed (total 0.33 parts by weight).
[0327] Examples 4 to 6: 72.67 wt% of polyvinyl butyral resin (A1), 27 wt% of 3g8 as a plasticizer, and 0.33 wt% of an additive were put into a twin-screw extruder (a) and extruded, and then formed into a film through a T-die (T-DIE). Before winding, different rollers or transfer conditions were used for embossing treatment as shown in Table 3 below, and the film with the surface pattern transferred was sampled in the form of a roll sample, thereby preparing the films of Examples 4 to 6. In the transfer conditions, the pressure condition remained unchanged, and the temperature condition adopted the temperature shown in Table 3 below. The thickness of the prepared film was 760 um and the width was 1.0 M.
[0328] Comparative Example 2: A film of Comparative Example 2 was prepared in the same manner as in Example 4, except that the embossing treatment was performed using a roll (ROLL 0) that was not subjected to fine pattern processing of projections and depressions.
[0329] Evaluation Example 2: Evaluation of physical properties
[0330] Surface roughness measurement
[0331] For the three-dimensional roughness, Mr1 value and Mr2 value were measured by using a measuring device according to ISO_25178. The three-dimensional roughness was measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) of Bruker in a vertical scanning interferometric mode.
[0332] Specifically, the measurement was performed using a 2x eyepiece and a 5x objective lens, and at this time, the area of 0 to 0.887 mm on the x-axis and 0 to 0.670 mm on the y-axis could be scanned. Under the same pattern, the measurement area was randomly determined, and the measurement was repeated 5 times, and the average of the 3 measured values excluding the maximum and minimum values was taken.
[0333] The following Table 3 shows the values of Sz, Mr1, Mr2, rev_Mr2, and Mr1-rev_Mr2 calculated based on the measurement results.
[0334] Edge Seal Evaluation:
[0335] Preparation of samples for evaluation 1): The films of the examples and comparative examples were cut into pieces with a width*length of 1000*1000 mm and then aged by leaving them at 20 degrees and 20 rh% for 2 days. A 300*300 mm test piece was cut based on the center portion in the width direction of the film, and three test pieces were cut in the same manner in the length direction.
[0336] The test piece was placed between two flat glass sheets with a thickness of 2.1T (T=mm, the same below) and pre-bonded. Three evaluation samples were prepared for each of the examples and comparative examples.
[0337] The width and length of a single evaluation sample were 300 mm, respectively, and the total length of the four sides of the edge of one sample was 1200 mm. Three evaluation samples were prepared for each of the examples and comparative examples, and the edge sealing was evaluated over a total of 3.6 m.
[0338] The pre-bonding process was performed by degassing at 20° C. for 5 minutes using a vacuum ring, and then maintaining at three different temperature intervals of 70° C., 85° C., and 100° C. for 15 minutes each.
[0339] Preparation of evaluation samples 2): A flat glass having a thickness of 2.1T was cut into a width*length of 300*300mm and then aged by leaving it at 25°C, 40rh% for 60 days. An evaluation sample was prepared using the aged flat glass in the same manner as in the preparation of the evaluation sample 1), however, the holding temperature after degassing was set to 85°C.
[0340] Evaluation of edge sealing degree): The evaluation samples were evaluated with the naked eye, and when the edge sealing was complete and the pattern was not visible at all, it was evaluated as 5 points, when the edge sealing degree was good and the pattern was faintly visible with the naked eye, it was evaluated as 4 points, when the edge sealing degree was ordinary and the pattern was visible with the naked eye, it was evaluated as 3 points, when the edge sealing degree was poor and the pattern was visible with the naked eye, it was evaluated as 2 points, and when the edge sealing degree was poor and the pattern was obviously visible with the naked eye, it was evaluated as 1 point, and the total score of the 3 samples is shown in the following Table 4.
[0341] Bubble Generation Evaluation
[0342] The evaluation samples of the examples and comparative examples that had completed preliminary bonding were compressed in an autoclave at 140°C and 1.2 MPa for 20 minutes to obtain bonded glasses that had completed main bonding. The time required for main bonding, including the heating time and the cooling time, was 90 minutes in total.
[0343] The number of bubbles generated in the bonding glass after the main bonding was confirmed with the naked eye. When the total number of bubbles confirmed in the three samples of the embodiment and the comparative example was 5 or less, it was marked as 5 points, when the total number of bubbles was 6 to 10, it was marked as 3 points, and when the total number of bubbles was 11 or more, it was marked as 1 point. The results are shown in Table 4.
[0344] [Table 3]
[0345]
[0346] [Table 4]
[0347]
[0348] Referring to Table 3, when comparing the Sz values of Examples 4 to 6 in which the roller surface is additionally processed with a fine pattern by sandblasting and grinding and Comparative Example 2, the maximum difference is only 5um. It can be seen that even if a fine pattern is additionally processed on the roller surface, the value of the surface roughness Sz will not change significantly.
[0349] In addition, in the case of Examples 4 to 6 where fine pattern additional processing was performed, the Mr1-rev_Mr2 value was measured to be 3.0 or more, whereas in the case of Comparative Example 2 where fine pattern additional processing was not performed, the Mr1-rev_Mr2 value was measured to be -1.3. Thus, when the roller surface is subjected to fine pattern additional processing, the density distribution of the convex valleys in the valley portion of the surface of the prepared film is relatively reduced, and the peak-to-valley distribution value is increased, and in this case, the edge sealing property confirmed by the pre-bonding property can be further improved.
[0350] Referring to Table 4, in the edge sealing evaluation, for Examples 4 to 6, scores of 12 or more were obtained under all conditions. On the contrary, for Comparative Example 2, the sample pre-bonded with ordinary glass at 70°C and the sample pre-bonded with aged glass at 85°C obtained scores of 5 or less. This shows that when additional processing of fine patterns is performed on the film, the edge sealing of the film can be improved.
[0351] In addition, in the bubble generation evaluation, Examples 4 to 6 obtained 5 points under all conditions. On the contrary, in the case of Comparative Example 2, except for the sample pre-bonded with ordinary glass at 100°C, scores below 3 were obtained. This shows that when additional processing of fine patterns is performed on the film, the degassing stability of the film can be improved.
[0352] It can be confirmed that even when the glass having a relatively uneven surface after the aging treatment is applied, the results of Examples 4 to 6 are more excellent than those of Comparative Example 2.
[0353] Preparation Example 3: Mold Processing
[0354] A fine pattern is further formed on the surface of the steel mold having a matte pattern in which dots are formed randomly, that is, an embossed shape.
[0355] A mold (Rz=50 μm) having concavoconvexities in a matte pattern morphology was used as MOL 0 .
[0356] MOLD 1 was prepared by subjecting the same mold as MOLD 0 to shot peening and sand blasting, respectively. Specifically, the shot peening was performed by direct pressure spraying particles having an average outer diameter of 50 um through a 140-mesh foreign matter removal filter at a distance of 15 to 20 cm at a spray pressure of 0.4 MPa. The angle between the matte pattern surface and the sprayed particles (or nozzle) was 90°. The sand blasting was performed by direct pressure spraying particles having an average outer diameter of 5 um through a 200-mesh foreign matter removal filter at a distance of 15 to 20 cm at a spray pressure of 0.4 MPa. The angle between the matte pattern surface and the sprayed particles (or nozzle) was 5 to 10°.
[0357] As shown in Table 5 below, the mold prepared by the above process was used in the examples.
[0358] Preparation Example 3: Preparation of membrane
[0359] The respective components used in the following Examples and Comparative Examples are as follows.
[0360] Polyvinyl butyral resin (A1) : Polyvinyl alcohol (PVA) with a polymerization degree of 1700 and a saponification degree of 99 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 20.3 wt % of hydroxyl groups, 78.9 wt % of butyral groups and 0.8 wt % of acetyl groups.
[0361] Preparation of additives: 0.1 parts by weight of Irganox 1076 as an antioxidant, 0.2 parts by weight of TINUVIN-328 as a UV absorber, and 0.03 parts by weight of magnesium acetate (Mg Acetate) as a bonding strength regulator were mixed and stirred in a rotating cup to be fully dispersed (total 0.33 parts by weight).
[0362] Preparation of sheets
[0363] Preparation of Sheet 1: 72.67 wt% of polyvinyl butyral resin (A1), 27 wt% of 3g8 as a plasticizer and 0.33 wt% of additives were put into a twin-shaft extruder, and then a mirror-finished sheet 1 was prepared through a T-die (T-DIE).
[0364] Preparation of Sheet 2: The sheet 2 was prepared in the same manner as the sheet 1, except that a die lip cooler was used at 15°C during the extrusion film-forming process to obtain a sheet 2 having melt fracture on the surface.
[0365] Transferring the pattern to the sheet
[0366] Example 7: Transferring a pattern onto the surface of the prepared sheet 1 by using MOLD 1.
[0367] Example 8: Transferring a pattern onto the surface of the prepared sheet 2 by using MOLD 1.
[0368] Comparative Example 3: A pattern was transferred onto the surface of the prepared sheet 1 by using MOLD 0.
[0369] Comparative Example 4: The prepared sheet 2 was used without transferring a pattern.
[0370] Evaluation Example 3: Evaluation of physical properties
[0371] Surface roughness measurement
[0372] For three-dimensional roughness, Svk, S*vk, A2 and Sz values were measured by using a measuring device according to ISO_25178. The three-dimensional roughness was measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) of Bruker through a vertical scanning interferometric mode.
[0373] Specifically, the measurement was performed using a 2x eyepiece and a 5x objective lens, and at this time, the area of 0 to 0.887 mm on the x-axis and 0 to 0.670 mm on the y-axis could be scanned. Under the same pattern, the measurement area was randomly determined, and the measurement was repeated 5 times, and the average of the 3 measured values excluding the maximum and minimum values was taken.
[0374] The following Table 5 shows the Svk, S*vk, A2, and Sz values calculated based on the measurement results.
[0375] Edge Seal Evaluation:
[0376] Preparation of samples for evaluation 1): The films of the examples and comparative examples were cut into pieces with a width*length of 1000*1000 mm and then aged by leaving them at 20 degrees and 20 rh% for 2 days. A 300*300 mm test piece was cut based on the center portion in the width direction of the film, and three test pieces were cut in the same manner in the length direction.
[0377] The test piece was placed between two flat glass sheets with a thickness of 2.1T (T=mm, the same below) and pre-bonded. Three evaluation samples were prepared for each of the examples and comparative examples.
[0378] The width and length of a single evaluation sample were 300 mm, respectively, and the total length of the four sides of the edge of one sample was 1200 mm. Three evaluation samples were prepared for each of the examples and comparative examples, and the edge sealing was evaluated over a total of 3.6 m.
[0379] The pre-bonding step was performed by degassing at 20° C. for 5 minutes using a vacuum ring, and then maintaining at two different temperature intervals of 70° C. and 100° C. for 15 minutes each.
[0380] Evaluation of edge sealing degree): The evaluation samples were evaluated with the naked eye, and when the edge sealing was complete and the pattern was not visible at all, it was evaluated as 5 points, when the edge sealing degree was good and the pattern was faintly visible with the naked eye, it was evaluated as 4 points, when the edge sealing degree was ordinary and the pattern was visible with the naked eye, it was evaluated as 3 points, when the edge sealing degree was poor and the pattern was visible with the naked eye, it was evaluated as 2 points, and when the edge sealing degree was poor and the pattern was obviously visible with the naked eye, it was evaluated as 1 point, and the total score of the 3 samples is shown in Table 6.
[0381] Bubble Generation Evaluation
[0382] The evaluation samples of the examples and comparative examples that had been pre-joined were compressed in an autoclave at 140°C and 1.2 MPa for 20 minutes to obtain joined glasses that had been mainly joined. The time required for the main joining, including the heating and cooling time, was 90 minutes in total.
[0383] The number of bubbles generated in the bonded glass after the main bonding was confirmed with the naked eye. When the total number of bubbles confirmed in the three samples of the embodiment and the comparative example was 5 or less, it was marked as 5 points, when the total number of bubbles was 6 to 10, it was marked as 3 points, and when the total number of bubbles was 11 or more, it was marked as 1 point. The results are shown in Table 6.
[0384] Evaluation of bubble generation in high temperature and high humidity environments
[0385] The pre-joined samples of the examples and comparative examples were placed in an environment of 85°C and 92 rh% for 120 hours, and then evaluated for bubble generation in the same manner as the bubble generation evaluation. The evaluation scores of the examples and comparative examples are shown in Table 6 below.
[0386] [Table 5]
[0387]
[0388] [Table 6]
[0389]
[0390] Referring to Table 5, the DSvk values of Examples 7 and 8 were measured to be less than 4, whereas the DSvk values of Comparative Examples 3 and 4 were measured to be greater than 6.
[0391] The DSvk / Svk values of Examples 7 and 8 were measured to be in the range of 0.30 to 0.60, whereas the DSvk / Svk values of Comparative Examples 3 and 4 were measured to be greater than 1.6.
[0392] The DSvk / Sz values of Examples 7 and 8 were measured to be 0.06 or less, whereas the DSvk / Sz values of Comparative Examples 3 and 4 were measured to be 0.09 or more.
[0393] The A2 values of Examples 7 and 8 were measured to be 0.18 or more, whereas the A2 values of Comparative Examples 3 and 4 were measured to be 0.15 or less.
[0394] The Sz values of the examples and comparative examples were measured to be in the range of 63 to 64.5. This shows that the Sz value does not change significantly even if a fine pattern is additionally processed on the embossed surface.
[0395] Referring to Table 6, in the edge sealing evaluation, the Examples obtained scores of 13 or more under all conditions, whereas Comparative Examples 3 and 4, when the pre-bonding was performed at a pre-bonding temperature of 70°C, obtained evaluation scores of only 12 points. This shows that in the case of a bonding film having a DSvk value of 6 μm or less by fine pattern additional processing, the edge sealing property is excellent even when the bonding process is performed at a low temperature.
[0396] In the evaluation of bubble generation, the evaluation scores of Examples and Comparative Examples were generally excellent, and in particular, Example 8 had an evaluation score of 5 points measured not only in a general environment but also in a case of long-term exposure to a high-temperature and high-humidity environment.
[0397] Preparation Example 4: Roller Processing
[0398] A steel roller having an embossed shape with a matte pattern in which dots are randomly formed is further provided with a fine pattern in the recessed portions, and a grinding treatment is performed on the raised portions.
[0399] like Figure 4 As shown, a roller having irregular concavoconvexities in a matte pattern morphology (Rz=50 um) was used as ROLL 0.
[0400] For the same roller as ROLL 0, ROLL 4a, ROLL 4b, and ROLL 4c were prepared by sandblasting the valleys and then grinding the peaks. Specifically, the valleys of the matte pattern were sandblasted, and the peaks of the matte pattern were ground. The sandblasting was performed by directly spraying particles with an average outer diameter of 5 μm through a 200-mesh foreign matter removal filter at a distance of 40 to 45 cm at a spray pressure of 0.4 MPa. The angle between the mold surface and the sprayed particles (or nozzle) was 85° or more and 105° or less.
[0401] Roll 4a was subjected to the above-mentioned sandblasting and grinding process once, Roll 4b was subjected to the above-mentioned sandblasting and grinding process three times, and Roll 4c was subjected to the above-mentioned sandblasting and grinding process ten times.
[0402] As shown in Table 7 below, the rollers prepared by the above process were applied to Examples or Comparative Examples.
[0403] Preparation Example 4: Preparation of membrane
[0404] The respective components used in the following Examples and Comparative Examples are as follows.
[0405] Polyvinyl butyral resin (A2) : Polyvinyl alcohol (PVA) with a polymerization degree of 1700 and a saponification degree of 99 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 19.6 wt % of hydroxyl groups, 80.0 wt % of butyral groups and 0.4 wt % of acetyl groups.
[0406] Polyvinyl butyral resin (B) : Polyvinyl alcohol (PVA) with a polymerization degree of 2400 and a saponification degree of 88 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 8.6 wt % of hydroxyl groups, 79.9 wt % of butyral groups and 11.5 wt % of acetyl groups.
[0407] Preparation of additives: 0.1 parts by weight of Irganox 1076 as an antioxidant, 0.2 parts by weight of TINUVIN-328 as a UV absorber, and 0.03 parts by weight of magnesium acetate (Mg Acetate) as a bonding strength regulator were mixed and stirred in a rotating cup to be fully dispersed (total 0.33 parts by weight).
[0408] Examples 9 to 11: Co-extrusion was performed by feeding 72.67 wt% of polyvinyl butyral resin (A2), 27 wt% of 3g8 as a plasticizer, and 0.33 wt% of an additive into a twin-shaft extruder (a), and 65 wt% of polyvinyl butyral resin (B) and 35 wt% of 3g8 as a plasticizer into another twin-shaft extruder (b). Molding was performed in the form of (A2) composition / (B) composition / (A2) composition by a feed block, and a film having a shape in which one end is thicker than the other end was formed by a T-die (T-DIE). Before winding, different rollers (ROLL4a, ROLL 4b, ROLL 4c) were applied to the upper and lower parts, respectively, as shown in Table 7 below, and the surface pattern was transferred to the film by a separate embossing process, and then sampled in the form of a roll sample, thereby preparing the films of Examples 9 to 11, respectively. At this time, in order to facilitate the transfer of the surface pattern of the film, the angles of both sides of the embossing roller were adjusted to 0.014° before transfer.
[0409] Comparative Example 5: A film of Comparative Example 1 was prepared in the same manner as in Example 9, except that the embossing treatment was performed using a roll (ROLL 0) that was not subjected to the additional processing of the upper and lower fine patterns.
[0410] Evaluation Example 4: Evaluation of physical properties
[0411] Wedge Angle Measurement
[0412] Since the thickness increase region of the evaluation film sample corresponds to the entire film, the thickness at both ends was measured and used as the Ha value and the Hb value. Specifically, the thickness at both ends was measured using a Mitsutoyo 547-401 thickness gauge.
[0413] After measuring the width between both ends of the evaluation film sample, the wedge angle measurement value was obtained by substituting the measured values Ha value, Hb value, and w value into the following third formula.
[0414] Form 3:
[0415]
[0416] In the third formula, Hb is the thickness of the thicker one of the two ends of the thickness-increased region, Ha is the thickness of the thinner one of the two ends of the thickness-increased region, and w is the width between the two ends of the thickness-increased region.
[0417] Surface roughness measurement
[0418] For the three-dimensional roughness, the A1 value and the A2 value were measured by using a measuring device according to ISO_25178. Specifically, the three-dimensional roughness was measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) of Bruker in a vertical scanning interferometric mode.
[0419] Specifically, the measurement was performed using a 2x eyepiece and a 5x objective lens, and at this time, the area of 0 to 0.887 mm on the x-axis and 0 to 0.670 mm on the y-axis could be scanned. Under the same pattern, the measurement area was randomly determined, and the measurement was repeated 5 times, and the average of the 3 measured values excluding the maximum and minimum values was taken.
[0420] Sz, A1 (peak region), A2 (valley region), and A2 / A1 values as the measurement results are shown in Table 7 below.
[0421] Edge Seal Evaluation:
[0422] Preparation of samples for evaluation 1): The films of the examples and comparative examples were cut into pieces with a width*length of 1000*1000 mm and then aged by leaving them at 20 degrees and 20 rh% for 2 days. A test piece of 900*300 mm was cut based on the center portion in the width direction of the film, and three test pieces were cut in the same manner in the length direction.
[0423] The test piece was placed between two sheets of flat glass having a thickness of 2.1T (T=mm) and pre-bonded. Three evaluation samples were prepared for each of the examples and comparative examples.
[0424] The width and length of a single evaluation sample were 900 mm and 300 mm, respectively, and the total length of the four sides of the edge of one sample was 2400 mm. Three evaluation samples were prepared for each of the examples and comparative examples, and the edge sealing was evaluated over a total length of 7.2 m.
[0425] The pre-bonding process was performed by degassing at 20° C. for 5 minutes using a vacuum ring, and then maintaining at three different temperature intervals of 70° C., 85° C., and 100° C. for 15 minutes each.
[0426] Preparation of evaluation samples 2): A flat glass having a thickness of 2.1T was cut into pieces having a width of 900 mm and a length of 300 mm, respectively, and then aged by leaving the pieces at 25°C and 40 rh% for 60 days. The evaluation samples were prepared using the aged flat glass in the same manner as in the preparation of the evaluation samples 1), however, the holding temperature after degassing was set to 85°C.
[0427] Evaluation of edge sealing degree): The evaluation samples were evaluated with the naked eye, and when the edge sealing was complete and the pattern was not visible at all, it was evaluated as 5 points, when the edge sealing degree was good and the pattern was faintly visible with the naked eye, it was evaluated as 4 points, when the edge sealing degree was ordinary and the pattern was visible with the naked eye, it was evaluated as 3 points, when the edge sealing degree was poor and the pattern was visible with the naked eye, it was evaluated as 2 points, and when the edge sealing degree was poor and the pattern was obviously visible with the naked eye, it was evaluated as 1 point, and the total score of the 3 samples is shown in Table 8.
[0428] Bubble Generation Evaluation
[0429] The evaluation samples of the examples and comparative examples that had completed preliminary bonding were compressed in an autoclave at 140°C and 1.2 MPa for 20 minutes to obtain bonded glasses that had completed main bonding. The time required for main bonding, including the heating time and the cooling time, was 90 minutes in total.
[0430] The number of bubbles generated in the bonding glass after the main bonding was confirmed with the naked eye. When the total number of bubbles confirmed in the three samples of the embodiment and the comparative example was 5 or less, it was marked as 5 points, when the total number of bubbles was 6 to 10, it was marked as 4 points, when the total number of bubbles was 11 to 15, it was marked as 3 points, and when the total number of bubbles was 16 or more, it was marked as 1 point. The results are shown in Table 8.
[0431] [Table 7]
[0432]
[0433]
[0434] [Table 8]
[0435]
[0436] Referring to Table 7 and Table 8, the wedge angles of the evaluation film samples prepared in Examples and Comparative Examples were all 0.014°.
[0437] When comparing the Sz values of Examples 9 to 11 and Comparative Example 5, in which the roller surface was subjected to additional processing of a fine pattern by sandblasting and grinding, the maximum difference was only 2.6 μm, so even if a fine pattern was additionally processed on the roller surface, the value of the surface roughness Sz did not change significantly. On the other hand, the A2 / A1 values of Examples 9 to 11 subjected to additional processing of a fine pattern were measured to be less than 1, whereas the A2 / A1 value of Comparative Example 5, which was not subjected to additional processing of a fine pattern, was measured to be 2.79, showing a huge difference.
[0438] Referring to Table 8, in the edge sealing evaluation, for Examples 9 to 11, scores of 10 or more were obtained under all conditions. On the contrary, for Comparative Example 5, the samples pre-bonded with ordinary glass at 85°C and 70°C and the sample pre-bonded with aged glass at 85°C obtained scores below 8, which shows that when additional processing of fine patterns is performed on the film, the edge sealing performance of the film can be improved.
[0439] In addition, in the bubble generation evaluation, for Examples 9 to 11, scores of 3 or above were obtained under all conditions. On the contrary, for Comparative Example 5, the score obtained in the case of pre-bonding with ordinary glass at 70°C and in the case of pre-bonding with aged glass at 85°C was only 1. This shows that when additional processing of fine patterns is performed on the film, the degassing stability of the film can be improved.
[0440] Preparation Example 5: Roller Processing
[0441] A steel roller having an embossed shape with a matte pattern in which dots are randomly formed is further provided with a fine pattern in the recessed portions, and a grinding treatment is performed on the raised portions.
[0442] like Figure 4 As shown, a roller having irregular concavoconvexities in a matte pattern morphology (Rz=50 um) was used as ROLL 0.
[0443] For the same roller as ROLL 0, ROLL 5a, ROLL 5b, and ROLL 5c were prepared by sandblasting the valleys and then grinding the peaks. Specifically, the valleys of the matte pattern were sandblasted, and the peaks of the matte pattern were ground. The sandblasting was performed by spraying particles with an average outer diameter of 5um through a 200-mesh foreign matter removal filter at a distance of 15 to 20cm at a spray pressure of 0.4MPa in a direct pressure manner. The angle between the matte pattern surface and the sprayed particles (or nozzle) was 85 to 105 degrees.
[0444] Roll 5a was subjected to the above-mentioned sandblasting and grinding treatment once, Roll 5b was subjected to the above-mentioned sandblasting and grinding treatment twice, and Roll 5c was subjected to the above-mentioned sandblasting and grinding treatment four times.
[0445] As shown in Table 9 below, the rollers prepared by the above process were applied to Examples or Comparative Examples.
[0446] Preparation Example 5: Preparation of membrane
[0447] The respective components used in the following Examples and Comparative Examples are as follows.
[0448] Polyvinyl butyral resin (A1): Polyvinyl alcohol (PVA) with a polymerization degree of 1700 and a saponification degree of 99 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 20.3 wt % of hydroxyl groups, 78.9 wt % of butyral groups and 0.8 wt % of acetyl groups.
[0449] Polyvinyl butyral resin (B) : Polyvinyl alcohol (PVA) with a polymerization degree of 2400 and a saponification degree of 88 and n-BAL were added and a conventional synthesis process was carried out to obtain a polyvinyl butyral resin containing 8.6 wt % of hydroxyl groups, 79.9 wt % of butyral groups and 11.5 wt % of acetyl groups.
[0450] Preparation of additives: 0.1 parts by weight of Irganox 1076 as an antioxidant, 0.2 parts by weight of TINUVIN-328 as a UV absorber, and 0.03 parts by weight of magnesium acetate (Mg Acetate) as a bonding strength regulator were mixed and stirred in a rotating cup to be fully dispersed (total 0.33 parts by weight).
[0451] Examples 12 to 14: 72.67 wt% of polyvinyl butyral resin (A1), 27 wt% of 3g8 as a plasticizer, and 0.33 wt% of an additive were fed into one twin-screw extruder (a), 65 wt% of polyvinyl butyral resin (B) and 35 wt% of 3g8 as a plasticizer were fed into another twin-screw extruder (b) for co-extrusion, and then molded in the form of (A1) composition / (B) composition / (A1) composition by a feed block, during which a film having a shape in which one end is thicker than the other end is formed by a T-die (T-DIE). Before winding, different rollers (ROLL 5a, ROLL 5b, ROLL 5c, refer to Table 9) were applied to the upper and lower parts, respectively, as shown in Table 9 below, and the surface pattern was transferred to the film by a separate embossing process, and then sampled in the form of a roll sample, thereby preparing the films of Examples 12 to 14, respectively. At this time, in order to facilitate the transfer of the surface pattern of the film, the angles of both sides of the embossing roller were adjusted to 0.014° before transfer. The thickness of the prepared film was 960um at one end and 1200um at the other end, and the width was 1.0M.
[0452] Comparative Example 6: A film of Comparative Example 6 was prepared in the same manner as in Example 12, except that the embossing treatment was performed using a roll (ROLL 0) that was not subjected to fine pattern processing of projections and depressions.
[0453] Evaluation Example 5: Evaluation of physical properties
[0454] Wedge Angle Measurement
[0455] Since the thickness increase region of the evaluation film sample corresponds to the entire film, the thickness at both ends was measured and used as the Ha value and the Hb value. Specifically, the thickness at both ends was measured using a Mitsutoyo 547-401 thickness gauge.
[0456] After measuring the width between both ends of the evaluation film sample, the wedge angle measurement value was obtained by substituting the measured values Ha value, Hb value, and w value into the following third formula.
[0457] Form 3:
[0458]
[0459] In the third formula, Hb is the thickness of the thicker one of the two ends of the thickness-increased region, Ha is the thickness of the thinner one of the two ends of the thickness-increased region, and w is the width between the two ends of the thickness-increased region.
[0460] Surface roughness measurement
[0461] For the three-dimensional roughness, Mr1 value and Mr2 value were measured by using a measuring device according to ISO_25178. The three-dimensional roughness was measured by using a non-contact three-dimensional roughness measuring instrument (3D Optical Microscopy, model Contour GT) of Bruker in a vertical scanning interferometric mode.
[0462] Specifically, the measurement was performed using a 2x eyepiece and a 5x objective lens, and at this time, the area of 0 to 0.887 mm on the x-axis and 0 to 0.670 mm on the y-axis could be scanned. Under the same pattern, the measurement area was randomly determined, and the measurement was repeated 5 times, and the average of the 3 measured values excluding the maximum and minimum values was taken.
[0463] The following Table 9 shows Sz, Mr1, Mr2, rev_Mr2, and Spv values calculated based on the measurement results.
[0464] Edge Seal Evaluation:
[0465] Preparation of samples for evaluation 1): The films of the examples and comparative examples were cut into pieces with a width*length of 1000*1000 mm and then aged by leaving them at 20 degrees and 20 rh% for 2 days. A test piece of 900*300 mm was cut based on the center portion in the width direction of the film, and three test pieces were cut in the same manner in the length direction.
[0466] The test piece was placed between two flat glass sheets with a thickness of 2.1T (T=mm, the same below) and pre-bonded. Three evaluation samples were prepared for each of the examples and comparative examples.
[0467] The width and length of a single evaluation sample were 900 mm and 300 mm, respectively, and the total length of the four sides of the edge of one sample was 2400 mm. Three evaluation samples were prepared for each of the examples and comparative examples, and the edge sealing was evaluated over a total length of 7.2 m.
[0468] The pre-bonding process was performed by degassing at 20° C. for 5 minutes using a vacuum ring, and then maintaining at three different temperature intervals of 70° C., 85° C., and 100° C. for 15 minutes each.
[0469] Preparation of evaluation samples 2): A flat glass having a thickness of 2.1T was cut into a width*length of 900*300mm and then aged by leaving it at 30°C, 50rh% for 60 days. An evaluation sample was prepared using the aged flat glass in the same manner as in the preparation of the evaluation sample 1), however, the holding temperature after degassing was set to 85°C.
[0470] Evaluation of edge sealing degree): The evaluation samples were evaluated with the naked eye, and when the edge sealing was complete and the pattern was not visible at all, it was evaluated as 5 points, when the edge sealing degree was good and the pattern was faintly visible with the naked eye, it was evaluated as 4 points, when the edge sealing degree was ordinary and the pattern was visible with the naked eye, it was evaluated as 3 points, when the edge sealing degree was poor and the pattern was visible with the naked eye, it was evaluated as 2 points, and when the edge sealing degree was poor and the pattern was obviously visible with the naked eye, it was evaluated as 1 point, and the total score of the 3 samples is shown in Table 10.
[0471] Bubble Generation Evaluation
[0472] The evaluation samples of the examples and comparative examples that had been pre-joined were compressed in an autoclave at 140°C and 1.2 MPa for 20 minutes to obtain joined glasses that had been mainly joined. The time required for the main joining, including the heating and cooling time, was 90 minutes in total.
[0473] The number of bubbles generated in the bonded glass after the main bonding was confirmed with the naked eye. When the total number of bubbles confirmed in the three samples of the embodiment and the comparative example was 5 or less, it was marked as 5 points, when the total number of bubbles was 6 to 10, it was marked as 4 points, when the total number of bubbles was 11 to 15, it was marked as 3 points, and when the total number of bubbles exceeded 15, it was marked as 1 point. The results are shown in Table 10 below.
[0474] [Table 9]
[0475]
[0476] [Table 10]
[0477]
[0478]
[0479] Referring to Table 9, the wedge angle of the samples of Examples and Comparative Examples was measured to be 0.014°.
[0480] When comparing the Sz values of Examples 12 to 14 in which the roller surface is additionally processed with a fine pattern by sandblasting and grinding and Comparative Example 6, the maximum difference is only 5.4um. Therefore, even if a fine pattern is additionally processed on the roller surface, the value of the surface roughness Sz will not change significantly.
[0481] In addition, for Examples 12 to 14 in which the fine pattern additional processing was performed, the Spv values were distributed in the range of 1.0 or more, and the Spv values gradually increased in the order of Examples 12, 13, and 14, whereas for Comparative Example 6 in which the fine pattern additional processing was not performed, the Spv value was measured to be less than 0. In the case where the fine pattern additional processing was performed on the roller surface, the density distribution of the convex valleys in the valley portion on the surface of the prepared film was relatively reduced, and the Spv value could be increased, and the more the number of fine pattern additional processings was performed, the more the Spv value increased.
[0482] Referring to Table 10, in the edge sealing evaluation, Examples 12 to 14 obtained scores of 11 or more under all conditions, whereas Comparative Example 6 obtained scores of less than 10 under all conditions except for the case of pre-bonding with ordinary glass at 100°C, and in particular, the average score of the case of pre-bonding with ordinary glass at a pre-bonding temperature of 70°C was only 5 points. This shows that a bonding film having an Spv value of 0% or more has stable edge sealing performance when pre-bonding is performed, and has excellent edge sealing performance when pre-bonding is performed at low temperatures.
[0483] In addition, in the evaluation of bubble generation, the examples obtained scores of 4 or more under all conditions, whereas the comparative example 6 obtained scores of 3 or less except for the sample pre-bonded with ordinary glass at 100°C, and the evaluation score of the case of pre-bonding with ordinary glass at 70°C was only 1 point. This shows that when the bonding film is subjected to fine pattern additional processing, the degassing stability of the film is improved, and in particular, excellent degassing properties can be achieved when pre-bonding is performed at low temperatures.
[0484] When the aged glass was used, the pre-joining evaluation score was measured to be 11 points or more and the bubble generation evaluation score was measured to be 4 points or more in the case of Examples 12 to 14, whereas the pre-joining evaluation score was only 5 points and the bubble generation evaluation score was only 1 point in the case of Comparative Example 6. It can be seen that when joining is performed using aged glass with uneven surfaces, if a joining film subjected to fine pattern additional processing is used for joining, stable edge sealing performance and degassing properties can be achieved.
[0485] As described above, although the preferred embodiments are described in detail, it should be understood that the scope of the present invention is not limited to the above embodiments, but various changes or modifications by those skilled in the art using the basic concepts of the present embodiment defined in the claims belong to the scope of the present invention.
Claims
1. A bonding film, wherein: include: A surface formed with an embossing having a regular pattern or an irregular pattern; The surface formed with the embossing has Mr1 value and Mr2 value, The rev_Mr2 value is obtained by subtracting the Mr2 value from 100%. The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value, Assuming the peak-to-valley distribution value is Spv, it is expressed by the following formula 1: The peak-to-valley distribution value of the surface formed with the embossing is greater than or equal to 0% and less than or equal to 25%, Formula 1: Spv=Mr1-rev_Mr2 In the first formula, The Spv is the peak-to-valley distribution value, The rev_Mr2 value is the value obtained by subtracting the Mr2 value from 100%. The Mr1 value is 10% or more, The Mr1 value and the Mr2 value are values evaluated according to ISO_25178.
2. The bonding film according to claim 1, wherein The Sz value of the surface formed with the embossing is 30 μm to 90 μm, The Sz value is a value evaluated according to ISO_25178.
3. A light-transmitting laminate, wherein: include: The first light-transmitting layer; a bonding film, located on one surface of the first light-transmitting layer; as well as The second light-transmitting layer is located on the bonding film, The bonding film includes a surface formed with embossing having a regular pattern or an irregular pattern; The surface formed with the embossing has Mr1 value and Mr2 value, The rev_Mr2 value is obtained by subtracting the Mr2 value from 100%. The Mr1 value of the surface formed with the embossing is equal to or greater than the rev_Mr2 value, Assuming the peak-to-valley distribution value is Spv, it is expressed by the following formula 1: The peak-to-valley distribution value of the surface formed with the embossing is greater than or equal to 0% and less than or equal to 25%, Formula 1: Spv=Mr1-rev_Mr2 In the first formula, The Spv is the peak-to-valley distribution value, The rev_Mr2 value is the value obtained by subtracting the Mr2 value from 100%. The Mr1 value is 10% or more, The Mr1 value and the Mr2 value are values evaluated according to ISO_25178.
Citation Information
Patent Citations
Interlayer for laminated glass and laminated glass
JP2001220183A
Multi-layer laminates with films embossed on one side, based on partially acetalated polyvinyl alcohol
KR101376061B1
Moving Conveyor System having Cooling Apparatus for airport baggage and control method thereof
KR1020190097413A
Method of detecting document placement direction of image forming apparatus
KR1020190103615A
Actuator with auxiliary motor
KR1020190105222A